Intrinsic proton conduction in 2D sulfonated covalent organic frameworks through a post-synthetic strategy. Issue 36 (9th September 2021) - Zhang, Yuwei; Li, Chunzhi; Liu, Zhaohan; Yao, Yuze; Hasan, Md. Mahmudul; Liu, Qianyu; Wan, Jieqiong; Li, Zhongping; Li, He; Nagao, Yuki
Abstract : A 2D sulfonated COF showed intrinsic proton conductivity up to 10 −3 at 25 °C and 100% relative humidity and high conductivity up to 10 −2 S cm −1 at 70 °C and 100% RH. Abstract : Two-dimensional covalent organic frameworks (2D COFs) have attracted much attention in proton conduction, owing to their regular pore channels and easy functionalization. However, most of the COFs required loading of proton carriers to achieve high proton conductivity. Here, we report the immobilization of flexible sulfonic acid groups on the channel walls of PyTTA–DHTA-COF (synthesized by condensation of 4, 4′, 4′′, 4′′′-(pyrene-1, 3, 6, 8-tetrayl)tetraaniline and 2, 5-dihydroxyterephthalaldehyde) via a simple post-synthetic modification strategy. The sulfonated COF showed intrinsic proton conductivity up to 10 −3 at 25 °C and 100% relative humidity (RH) and high conductivity up to 10 −2 S cm −1 at 70 °C and 100% RH without the introduction of any non-covalent acid molecules or imidazole derivatives.